ANALISIS PENGARUH KEPEMIMPINAN, SUPERVISI AKADEMIK DAN MOTIVASI KERJA TERHADAP KINERJA GURU MTSN DI KECAMATAN BATANG ALAI SELATAN HULU SUNGAI TENGAH KALIMANTAN SELATAN - Sahibul Fajeri (JURNAL KINDAI, 2023)
This study aims to analyze the Influence of Leadership, Academic Supervision and Work Motivation on MTsN Teacher Performance in Batang Alai Selatan Hulu Sungai Tengah District. This research uses quantitative methods with a correlational type of research. The study population was 62 people and the sampling technique was saturated, which was the entire population of 62 people. Data collection techniques using questionnaires. The independent variables consist of Leadership, Academic Supervision and Work Motivation and the dependent variable of Teacher Performance. The data analysis technique uses multiple regression analysis, with hypothesis tests: F-test for simultaneous and t-test for partial and Î² test for dominant influence. The results found that the variables of leadership, academic supervision and work motivation had a significant effect on teacher performance, both simultaneously and partially. Of the three variables above, the variable that has a dominant influence on teacher performance is the leadership variable. Keywords: Leadership, Academic Supervision, Work Motivation and Teacher Performance